ETIKA PENDIDIKAN DALAM PEMIKIRAN AL-GHAZALI DAN KI HADJAR DEWANTARA: SEBUAH TELAAH PENGEMBANGAN PENDIDIKAN DI INDONESIA - Indah, Astrid Veranita (Aqidah-ta: Jurnal Ilmu Aqidah, 2021)
This study discusses the development of globalization, advances in science and technology that have an impact on human life. Ease of transportation, communication and access to education are positive impacts. Meanwhile, the degradation of moral values, namely individualistic, selfish, and competitive attitudes is a negative influence on the development and advancement of science. Moral education and among system education is an ideal educational alternative in facing the development of technology in Indonesia. Moral education according to al-Ghazali, teaches a child to understand the Qur'an and Hadith from an early age. By learning religion from an early age, children are able to strengthen beliefs. The basic character of children who are mature and supported by strong religious beliefs are able to avoid the bad effects of globalization. Meanwhile, among system education according to Ki Hadjar Dewantara is education that fosters mutual respect for fellow human beings. Appreciating and respecting fellow human beings will foster a sense of humanity and humanize humans, thus avoiding individualism, egoism, and competition between individuals.